Germline and reproductive tract effects intensify in male mice with successive generations of estrogenic exposure. - Tegan S Horan; Alyssa Marre; Terry Hassold; Crystal Lawson; Patricia A Hunt (PLoS Genetics)
The hypothesis that developmental estrogenic exposure induces a constellation of male reproductive tract abnormalities is supported by experimental and human evidence. Experimental data also suggest that some induced effects persist in descendants of exposed males. These multi- and transgenerational effects are assumed to result from epigenetic changes to the germline, but few studies have directly analyzed germ cells. Typically, studies of transgenerational effects have involved exposing one generation and monitoring effects in subsequent unexposed generations. This approach, however, has limited human relevance, since both the number and volume of estrogenic contaminants has increased steadily over time, intensifying rather than reducing or eliminating exposure. Using an outbred CD-1 mouse model, and a sensitive and quantitative marker of germline development, meiotic recombination, we tested the effect of successive generations of exposure on the testis. We targeted the germline during a narrow, perinatal window using oral exposure to the synthetic estrogen, ethinyl estradiol. A complex three generation exposure protocol allowed us to compare the effects of individual, paternal, and grandpaternal (ancestral) exposure. Our data indicate that multiple generations of exposure not only exacerbate germ cell exposure effects, but also increase the incidence and severity of reproductive tract abnormalities. Taken together, our data suggest that male sensitivity to environmental estrogens is increased by successive generations of exposure.